2006
DOI: 10.1016/j.mcn.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species modulate the differentiation of neurons in clonal cortical cultures

Abstract: Reactive oxygen species (ROS) are important regulators of intracellular signaling. We examined the expression of ROS during rat brain development and explored their role in differentiation using cortical cultures. High levels of ROS were found in newborn neurons. Neurons produced ROS, not connected with cell death, throughout embryogenesis and postnatal stages. By P20, ROS-producing cells were found only in neurogenic regions. Cells with low levels of ROS, isolated from E15 brains by FACS, differentiated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
82
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 90 publications
3
82
0
Order By: Relevance
“…The present results suggest that Apocynin and 5-HD act by stimulating differentiation of mesencephalic precursors toward the DA phenotype. The results are consistent with those of previous studies, which have suggested that the redox state modulates differentiation of mesencephalic precursors (Studer et al, 2000;Rodriguez-Pallares et al, 2001Tsatmali et al, 2005), and with those of studies that have suggested that ROS levels affect the phenotype of cells in culture (Li et al, 2006;Xiao et al, 2009), including neurons (Tsatmali et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present results suggest that Apocynin and 5-HD act by stimulating differentiation of mesencephalic precursors toward the DA phenotype. The results are consistent with those of previous studies, which have suggested that the redox state modulates differentiation of mesencephalic precursors (Studer et al, 2000;Rodriguez-Pallares et al, 2001Tsatmali et al, 2005), and with those of studies that have suggested that ROS levels affect the phenotype of cells in culture (Li et al, 2006;Xiao et al, 2009), including neurons (Tsatmali et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the increase in the number of TH-ir neurons observed after treatment with Apo or 5-HD may be due to a decrease in ROS-induced cell death and the consequent increase in cell survival rate. However, several previous studies have shown that oxidative stress is not a major cause of apoptotic cell death in aggregates of neural progenitors unless they are challenged with stress inducers (Lee et al, 2003;Tsatmali et al, 2006). In addition, several previous studies have demonstrated that cell death of neural precursors within proliferating clusters is relatively rare compared with that of dissociated cells (Studer et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS production has mainly been related to cell growth, 23 with only a few reports addressing their involvement in the triggering of specific differentiation programmes being available. 6,7,24 Although ROS production in response to haematopoietic cytokines has long been known, 10 little is known about their possible involvement in haematopoiesis. Accordingly, we were therefore prompted to study this issue in depth using megakaryocytic differentiation as a system.…”
Section: Discussionmentioning
confidence: 99%
“…4 A few recent reports have described the relevance of NADPH oxidase ROS production in the differentiation of different kind of cells. 6,7 Therefore, it is tempting to speculate that NADPH ROS production might be a general mechanism common to all types of cell differentiation. However, to confirm this, further studies should be carried out on other types of cell differentiation.…”
mentioning
confidence: 99%